Antibodies in the control of type I diabetes - Chatenoud, Lucienne (Henry Stewart Talks, 2007)
The history of IDDM, Autoimmune origin of human type 1 diabetes, Natural history and pathophysiology of type 1 diabetes, The role of regulatory T-cells in the control of type 1 diabetes, Objectives of immunotherapy in insulin-dependent diabetes mellitus, The use of immunosuppressants in type 1 diabetes, The use of tolerance promoting monoclonal antibodies in type 1 diabetes: the case of CD3 antibodies
Reviewed at 2019/06/13, Archived at 2020/08/31